ETUDE DE L`ELECTRIFICATION DES SYSTEMES FERROVIAIRES EN ALGERIE - Hakima Lachgar; Yousra Tradkhoudja (My University, 2023)
Railway electrification offers several advantages in terms of performance and reliability Electric trains are generally faster and provide smoother acceleration compared to diesel-powered trains, helping to reduce journey times and improve the passenger experience. In addition, electric motors are often quieter than diesel engines, thus reducing noise pollution along railway tracks and improving the comfort of local residents. To this end, the objective of our research consists essentially in simulating the direct current (DC) railway electric traction chain that exists in the Souk-Ahras station. Our result of simulations under the Simulink environment of MATLAB for a chosen operating mode has allowed us to know the harmonics generated by the rectifier group of the substation and propagated towards the electrical network. At the end of our study, we proposed a more adequate solution to this situation consists in installing two resonant filters tuned to the 11th and 13th harmonics on the output of the transformer, this solution reduces the rate of harmonic distortion to an acceptable value lower than the IEEE-512 standard. ---------------------------------------------------------------------------------------- تقدم كهربة السكك الحديدية العديد من المزايامن حيث الأداء والموثوقية. القطارات الكهربائية أسرع بشكل عام وتوفر تسارعًا أكثر سلاسة مقارنة بالقطارات التي تعمل بالديزل، مما يساعد على تقليل أوقات الرحلات وتحسين تجربة الركاب. بالإضافة إلى ذلك، غالبًا ما تكون المحركات الكهربائية أكثر هدوءًا من محركات الديزل، وبالتالي تقليل التلوث الضوضائي على طول خطوط السكك الحديدية وتحسين راحة السكان المحليين. تحقيقًا لهذه الغاية، يتمثل هدف بحثنا بشكل أساسي في محاكاة سلسلة الجر الكهربائي للسكك الحديدية للتيار المباشر (DC) الموجودة في محطة سوق أهراس. سمحت لنا نتيجة عمليات المحاكاة التي أجريناها في بيئة Simulink لـ MATLAB لوضع التشغيل المختار بمعرفة التوافقيات التي تم إنشاؤها بواسطة مجموعة المقومات للمحطة الفرعية وانتشارها نحو الشبكة الكهربائية. في نهاية دراستنا، اقترحنا حلاً أكثر ملاءمة لهذا الموقف يتمثل في تثبيت مرشحين رنانين تم ضبطهما على التوافقيات 11 و13 على خرج المحول، وهذا الحل يقلل من معدل التشويه التوافقي إلى قيمة مقبولة أقل من معيار IEEE-512 ------------------------------------------------------------------------------------------ L'électrification des chemins de fer offre plusieurs avantages en termes de performance et de fiabilité. Les trains électriques sont généralement plus rapides et offrent une accélération plus régulière par rapport aux trains à moteur diesel, ce qui permet de réduire les temps de trajet et d'améliorer l'expérience des passagers. De plus, les moteurs électriques sont souvent plus silencieux que les moteurs diesel, réduisant ainsi la pollution sonore le long des voies ferrées et améliorant le confort des riverains.A cet effet l’objectif de notre recherche, consiste essentiellement, à simuler la chaine de traction électrique ferroviaire à courant continu (CC) qui existe dans la gare de Souk-Ahras. Notre résultat de simulations sous l’environnement Simulink de MATLAB pour un régime de fonctionnement choisi nous a permet de connaitre les harmoniques générés par le groupe redresseur de la sous-station et propagés vers le réseau électrique. En fin de notre étude nous avons proposé une solution plus adéquate a cette situation consiste à installer deux filtres résonnants accordés aux harmoniques 11th et 13thsur la sortie du transformateur,cette solution réduit le taux de distorsion d’harmonique à une valeur acceptable inferieur à la norme IEEE-512.